Consumer Grade 3D Printing: Comparative Mechanical Properties of Material Extrusion and Vat Photopolymerization Systems - Yopi Yusuf Tanoto; Ivan Christian Hernando; Victor Yuardi Risonarta; Nicholas Adriel Sugiarto; Louis Soesanto (Institute of Research and Community Outreach, Petra Christian University, 2026)
Additive manufacturing (AM) technologies can generally be divided into industrial-grade systems and consumer-grade machines, the latter being more cost-effective and accessible to a broader user base. Within the consumer segment, the most prevalent methods are fused deposition modelling (FDM) and LCD-based vat photopolymerization. Although FDM has been extensively studied, direct performance comparisons between material extrusion (ME) and vat photopolymerization (VP) remain relatively scarce. This study addresses this gap by evaluating the mechanical behavior of both technologies. The results show that LCD-based printing demonstrates superior performance in certain mechanical aspects (elongation), while both entry-level materials achieved comparable tensile strengths of approximately 31.5 MPa. In contrast, the flexural strength was higher in the specimens produced by ME, indicating that each process carries distinct advantages depending on the application.